The Influence of Sales Promotion and Customer Relationship Management on Customer Purchase Decisions for Products of PT. Auto Star Mandiri Teknotama Medan - Hommy Dorthy Ellyany Sinaga; Irvan Rolyesh Situmorang; Zavier Tantra (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Autostar Mandiri Teknotama (AMT), a car spare parts distributor established in 1999, has experienced a decline in purchases due to ineffective sales promotions and weak implementation of Customer Relationship Management (CRM), making it difficult to maintain customer loyalty amid increasing competition in similar products. The purpose of this study is to determine the effect of sales promotion and customer relationship management on purchasing decisions. The research uses a quantitative method to investigate the stated problems. The population in this study consists of all customers who made purchases from the company during the 2024 period, totaling 153 stores that have been subscribed for more than one year. Given that the population consists of 153 stores, the sampling technique used is a saturated sample, in which the entire population is taken as the sample. The results show that both partially and simultaneously, sales promotion and customer relationship management significantly influence purchasing decisions.